Biological and Thrombolytic Properties of Proenzyme and Active Forms of Human Urokinase – I. Fibrinolytic and Fibrinogenolytic Properties in Human Plasma In Vitro of Urokinases Obtained from Human Urine or by Recombinant DNA Technology - Zamarron, C; Lijnen, H R; Van Hoef, B; Collen, D (Thrombosis and Haemostasis, 1984)
The fibrinolytic and fibrinogenolytic properties of recombinant pro-urokinase (Rec-pro-UK) and recombinant urokinase (Rec- UK) obtained by expression of the human urokinase cDNA in E. coli, were compared with those of natural urokinase (Nat-UK) of urinary origin and of tissue-type plasminogen activator (t-PA) in a system, composed of a radioactive human plasma clot immersed in citrated human plasma.The specific fibrinolytic effects of Nat-UK, Rec-pro-UK and Rec-UK were very similar, causing significant clot lysis at concentrations of 100 IU/ml plasma or more. t-PA caused equivalent degrees of clot lysis at 10-fold lower concentrations.Activation of the fibrinolytic system in the plasma (fib- rinogenolysis), was not observed with t-PA in concentrations which induced complete clot lysis within 5 hr (20-30 IU/ml plasma). With Nat-UK and Rec-UK, all concentrations which caused significant clot lysis (100-200 IU/ml plasma) also caused extensive activation of the plasma fibrinolytic system. With Rec- pro-UK an intermediate response was obtained. The highest amounts required for complete clot lysis in 5 hr (200 IU/ml plasma) also caused significant fibrinogenolysis. At intermediate concentrations (50-100 IU/ml), however, significant clot lysis (40-80%) was observed without systemic fibrinolytic activation.
Keywords: Recombinant pro-urokinase; Fibrinolytic versus fibrinogenolytic ratio; Clot-selectivity; Inhibition of urokinase in plasma